(untitled) (Sociologisk Forskning, 2004)
Young people’s attitudes towards the Swedish welfare state’s expenditures are scrutinized in this study. Data from Statistics Sweden Survey of Living Conditions was used and a total of 5732 respondents aged 19 to 65, out of which 1106 were aged 19-30 years old, answered questions regarding what expenditures they considered should increase or decrease. The results show that there is self-interest in attitudes to the distribution of expenditures and substantial age-differences. Young people were more positive concerning expenditures towards the support argued important for establishment. Actual monetary transfer was not distinguishing between ages, therefore the situation of real or potential risk-exposure characteristic for youth was argued what was explaining the age-difference in attitudes. The results support the life-phase effect rather than the generation effect — individualizations achievement orientation — in the distribution of attitudes towards the Swedish welfare states expenditures.